The study compared stress levels among individuals with and without a history of coronavirus infection in students at Faculty of Nursing Buriram Western University - Phontip, Kittiphong; Meesap, Sudarat; Yodyothi, Ladawan; Kunachon, Puncharat; Aonudom, Yuwadee; Wuttisarn, Tanaporn; Seewas, Pasinee (RATANABUTH JOURNAL, 2022)
The study compared stress levels among individuals with and without a history of coronavirus infection in Nursing students Western University. This aim to study stress levels of individuals with and without a history of coronavirus infection and compared that. This research was descriptive research. The sample group used in the study were students of the Faculty of Nursing, Buriram, Western University, consisting of people with a history of infection and without history of coronavirus infection. The sample size was calculated by using the sample size calculation to test the hypothesis of differences in the mean of the two independent populations. A total of 100 samples were obtained from each group. The samples were selected using stratified sampling. The results showed that: The stress levels of individuals with a history of coronavirus infection. The stress level was 45.92%. The stress was high. And Persons without history of coronavirus infection the stress level was 43.92 percent. Stress was high. When comparing stress among individuals with and without a history of coronavirus infection in the students of the Faculty of Nursing, Buriram, Western University found no difference.